Developing students’ speaking skills through storytelling: Story-based pedagogy in Indonesian elementary school EFL context - LestariMayang Sri; AnanthiaWinti; SilawatiEndah; Mirawati (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
This research is motivated by the importance of English as one of the means of communication in applying 21st-century skills. Therefore, English needs to be taught as early as possible so that children can get used to communicating in English. However, in the implementation of English learning in the Indonesian primary school context, teachers find difficulties in improving students’ speaking skills. Therefore, this research was carried out to overcome obstacles in the English learning process, especially in speaking skills. The implementation of Story-Based Pedagogy (SBP) in 5th-grade elementary school was proposed to overcome the obstacles. This research aimed to identify the implementation of SBP to improve the speaking skills of 5th-grade elementary school students in English lessons. Action research was employed in this study, with a descriptive qualitative research design. This study involved 29 5th-grade primary school students. The result of the study showed that all the students improved their speaking skills. The students’ improvement in speaking performance was prominently shown in their English vocabulary mastery, pronunciation, fluency, and confidence.